Variability of resistance exercise velocity measures in rugby league players. - Callaghan, D. E.; Elsworthy, N.; Guy, J. H.; Kean, C. O. (Journal of Australian Strength and Conditioning, 2020)
The velocity of resistance exercises has been found to be an effective means to monitor changes in the performance and neuromuscular fatigue of athletes. While the reliability of the devices used to measure velocity has been thoroughly researched, the variability in the athlete`s performance of the exercises between sessions should also be considered when utilising measures of velocity to inform coaching decisions. Thus, the aim of this study was to investigate the between session reliability of resistance exercise velocity measures from a three-dimensional (3D) motion capture system, considered to be the gold standard of velocity measurement.